Cell wall composition in the classification of Gram positive anaerobes1 - CUMMINS, C. S. (International Journal of Systematic and Evolutionary Microbiology, 1970)
ABSTRACT Four groups of strains of Clostridia and anaerobic corynebacteria were examined by chemical and antigenic cell wall analysis. In each group it was possible to identify more than one pattern of cell wall sugar components, and these sugar patterns show a high degree of correlation with the subgroups revealed by cell wall agglutination tests. In the two groups tested, DNA/DNA homology tests showed that strains with the same cell wall sugar pattern had a high degree of homology (80-100%).